INSTITUTE OF PROBATION SERVICE IN THE RUSSIAN FEDERATION - Nesterov A.Y. (Scientific Journal of Pedagogy and Economics, 2020)
In the article, based on the results of an empirical study, the development prospects of the probation service institute in the Russian Federation are presented. The probation service in Russia will focus on the development of juvenile probation in the Russian Federation, which will become the basis for ensuring the successful social adaptation of juvenile offenders in the post-prison period and their subsequent reintegration into modern Russian society. For the first time, the author of the article proposes the structure of the new Federal Law “On the Probation Service in the Russian Federation”. In the development and subsequent discussion in parliament of the Russian Federation of this bill, the author of the publication suggests paying attention to the section "The main activities of rehabilitation centers of the Federal Security Service of Russia". It is determined that the criminal-executive and criminal legislation in Russia as a whole establishes the principle of differentiating the appointment and execution of criminal punishment, especially for juvenile convicts serving criminal sentences in prisons. The problem of legal regulation of the activities of the organizations considered here is extremely acute today. The problem of legal regulation is associated with the post-prison adaptation of persons released from prison. Taking into account the experience of some foreign sovereign states of Asia and Europe, it is necessary to complete the work that has already begun and to adopt the Federal Law on Post-Prison - Social Adaptation of Persons Exempted from Criminal Punishment. The author also determined that penitentiary re-socialization of a convicted person is oriented towards full or partial restoration of social (life) skills, which allows a minor convicted person to reintegrate into society in the postprison period, independently navigate the issues of obtaining a profession, employment, creating his own family, etc. A juvenile convict, while in prison, partially or completely loses family ties, loses contact with the outside world, friends, acquaintances, and even close relatives turn away from the teenager. But they are necessary for the teenager throughout the entire period of stay in places of deprivation of liberty, and especially after release from the colony in the first post-prison period. The author also proved that a teenager receives in prisons the necessary primary professional, cultural and aesthetic educational, social skills that will guide him in the process of social adaptation in one or another sphere of life. The material in this article does not contain information (information) relating to state secrets of the Russian Federation.